#TITLE_ALTERNATIVE# - FERDIANSYAH (NIM : 12012010), KURNIA
Bandung Barat area is one of the most landslide occurrence in Indonesia. Administratively, the study area is located in the area Wangunsari Village, West Bandung District, West Java Province. This study divided into two subdivisions. The first study was build a landslide susceptibility model for the Wangunsari area and surrounding. Parameters considered to be potential control of slope failure within this area were lithology, elevation, land cover type, slope gradient, slope orientation, curvature, distance form stream,wetness (TWI) and vegetation index (NDVI). There were 69 total of landslide were identified in this study area. Landslide data was randomly divided into a landslide train (60%) and landslide test (40%). The quantitative relationship between each point of landslide and parameters mentioned above was established by WoE (Weight of Evidence) in each class. Summing weighted parameter layers, that value reclassified into 4 susceptibility classes, high (18,8%), medium (11,3%), low (17,2%), and very low (52,7%). The second study was aimed to analyze the stability of slope from selected zone. Slope stability analysis was conducted with the consideration of the geometry slope and geological subsurface condition, such as stratigraphy and physical mechanical properties of soil/rock. Stratigrafi of the research area consisted of sandy soil layer (γ = 15,57 15,59 kN/m3, ϕÃ‚Â’ = 17,34-23Ã‚Â°, cÃ‚Â’ = 0,62-3,94 kN/m2), soil type classified into SM, thickness is Ã‚Â±2,5 m; clayley soil layer (γ = 13,53 kN/m3, ϕÃ‚Â’ = 15Ã‚Â°, cÃ‚Â’ = 4,8 kN/m2), soil type classified into MH & OH, thickness is Ã‚Â±5 m; Tuf Breccia, grey-brownish, granule-pebble grain size, matrix Tuff, igneous rock fragmen, thickness is Ã‚Â±10 m, this layer classified into Beser Formation; Andesit Breccia, grey-black, gravel-cobble, angular, compact, open fabric, matrix mineral mafic sand-clay, this layer classified into Beser Formation. The geotechnical analyses were performed by utilizing SLIDE, limit equilibrium software. Natural slopes in research area had variedsafety factor values from 1,03 Ã‚Â– 1,42. Safety